Impact of industrial pollution on children's lungs: A comparative analysis of pulmonary function in critically polluted and non-polluted areas in western India - Rekha Kashyap; Ankit Sheth; Rupal Thasale; Moinuddhin Mansuri; Ankit Viramgami (Elsevier, 2023)
Background: Air pollution is a pressing global health concern, particularly in low- and middle-income countries like India. Children living near industrialized and critically polluted areas (CPAs) face heightened health risks due to their developing respiratory systems. This study aimed to assess the impact of industrial pollution on children's lung function in a CPA in western India. Methodology: The study evaluated 362 children studying in 5th to 7th standard from both a CPA and a relatively non-polluted area (NPA) for comparison. Ambient and indoor air quality measurements were taken, and pulmonary function tests were conducted to assess lung health. Group difference and regression analysis were performed with SPSS 26.0. Results: The CPA group showed significantly higher air pollution levels and a higher prevalence of obstructive and restrictive patterns in pulmonary function compared to the NPA group. The findings also revealed that children residing in CPA exhibited a significant decline of 530 ml forced expiratory flow rate (FEF 25-75%), and a reduction of 3.9% FEV1/FVC ratio when compared to children residing in relatively NPA. Conclusion: While this study's cross-sectional design has limitations, it provides valuable evidence of the impact of air pollution on children's lungs in a semi-urban industrialized area. To mitigate these health risks, integrating respiratory health check-ups, including pulmonary function tests, in existing health programs, like Rastriya Bal Swasthya Karyakram (RBSK), is recommended for early detection and intervention. Implementing initiatives such as enhancing green belts around schools and continuous air quality monitoring will be crucial.